effect work stress in performance of employees In The general company for vegetable oil industry - علي, شفاء محمد; موسى, وسام ابراهيم (Journal of Economics and Administrative Sciences, 2015)
This research theme of the pressures of work , which is one of the important topics in order to recognize the reality of( influencing the pressures of work in the performance of employees in the General Company for Vegetable Oil Industry in Baghdad )through the statement of the existence of the correlation and influence whether or not the statement of the strength of this relationship and its impact in the case of its existence has been provided as part of my Search for variables and their removal in front of the Sub- scientific aspect has been the distribution of the questionnaire on a sample of( 62) people working in the company Mint distributors on several sections where.Formed resolution of two sets of the first questions are for general information The second is to measure the research variables of the independent variable which is the pressures of work and the measured set of questions fall within the 11 dimension , some of the pressures of work internal , namely, ( role ambiguity , role conflict , workload , physical work environment , technology , organizational structure , responsibility towards others ) and some of the external pressures which (economic conditions , political conditions , social conditions cultural conditions) the dependent variable is the performance of employees, who represent the six dimensions are ( productive, labor turnover , absence of staff, innovation , quality  ,satisfaction of job )After collecting and unloading data processing program, the statistical (spss) results showed a positive relationship to the pressures of work in the performance of employees, as well as having a positive impact to the pressures of work in the performance of employees , and in the light of the results researcher reached the conclusions presented on the basis of which the recommendations of the most important.- The need to pay greater attention to the pressures of work and investment to paralyze positive.- The division of the business is just the employees of the company researched.- State support for the company's products for the protection of the local product.He also proposed to conduct research concerning the same subject last sector as well as to conduct research to other dimensions to the pressures of work and the performance of others.